Being Political Protagonists: Activist Trajectories and Gender Awareness of Female Chileans Exiled in Costa Rica. - Ramírez‐Hernández, Marcela (Bulletin of Latin American Research, 2026)
This article reconstructs the political trajectories of Chilean exiled women settling in Costa Rica. It analyses the manifestations and transmutations of their political praxis before, during and after the period of ostracism, based on life stories reconstructed through semi‐structured interviews with several women who began militancy before the 1973 coup d'état and are still active in the struggles for memory. Analysis shows how political praxis during exile facilitated alternative ways of conceiving citizenship, linking transnationally with solidarity networks and making their healing process a political instrument. During exile, the intersection between their background of militancy and detention, their political practices and social contexts promoted the development of gender perspectives that explain and redefine traumatic experiences.